2017
DOI: 10.1007/s12663-017-1036-5
|View full text |Cite
|
Sign up to set email alerts
|

Tension Pneumocephalus—A Rare Complication of Craniofacial Fracture: Report and Review

Abstract: The term tension pneumocephalus (TP) means raised intracranial pressure due to air in the cranial cavity. This presentation is a rare case report and review on TP. Decompressing this raising intracranial pressure is a surgical emergency. Therefore, this presentation emphasises the importance of timely identification and management of TP in saving life. In this case, the acute signs of raising intracranial pressure were identified and promptly addressed surgically along with the maxillofacial injury management.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Only a handful of case reports have described about the frontal sinus osteomyelitis following mucormycosis [8][9][10][11] . Mucormycosis usually affects the nose and paranasal sinuses; the disease can spread via direct extension or by hematogenous spread.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of case reports have described about the frontal sinus osteomyelitis following mucormycosis [8][9][10][11] . Mucormycosis usually affects the nose and paranasal sinuses; the disease can spread via direct extension or by hematogenous spread.…”
Section: Discussionmentioning
confidence: 99%
“…Sahoo et al reported a case of isolated frontal sinus mucormycosis that was accessed by coronal approach and after debridement of necrotic tissue, pericranial osteoplastic flap was used for obliteration. [ 8 ] Isolated involvement presents with non-specific symptoms of frontal headache leading to late recognition and usually with orbital or intracranial complications as a first clinical sign. [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tension pneumocephalus is a potentially life-threatening complication that presents with nonspecific symptoms such as headache, coma, and hemiparalysis, alongside deteriorating GCS, and it requires emergent decompression [ 12 , 13 ]. A few theories that highlight the development of tension pneumocephalus include the “ball valve” theory of Dandy and the inverted bottle cap effect theory.…”
Section: Discussionmentioning
confidence: 99%
“…The inverted bottle cap theory postulates that trauma within the cranium leads to decreased intracranial pressure, resulting in a vacuum that causes an inflow of air [ 1 ]. Volume of as little as 6.5 ml of air has been demonstrated to be discernible enough to cause tension pneumocephalus [ 12 ]. The treatment of tension pneumocephalus arises from a timely recognition of its classic imaging phenomena, known as the “Mount Fuji” sign on a CT of the brain [ 14 ].…”
Section: Discussionmentioning
confidence: 99%